IMPLEMENTASI PEMBELAJARAN ABAD 21 MELALUI KERANGKA COMMUNITY OF INQUIRY DENGAN MODEL THINK PAIR SHARE - Nila Arianti; Dias Aziz Pramudita (Jurnal Visi Ilmu Pendidikan, 2022)
21st century education is expected to produce human resources who have critical, creative, communicative, and collaborative thinking skills. The education system in Indonesia must be able to adapt to equip students with the required competencies. One of the right steps to support the mastery of 21st century skills is to apply the Community of Inquiry learning framework with the Think Pair Share model. The purpose of the research in this article is two. 1) Review the concept of the Community of Inquiry framework and the Think Pair Share learning model. 2) Describe the application of 21st century learning through the Community of Inquiry framework with the Think Pair Share model. The research method used is the qualitative method. Data collection techniques use observation, documentation, and interviews. The results of the research in this article are two, namely 1) Knowing the concept of the Community of Inquiry framework and the Think Pair Share learning model. 2) Application of 21st century learning through the Community of Inquiry framework with the Think Pair Share model.AbstrakPendidikan abad 21 diharapkan dapat menghasilkan sumber daya manusia yang memiliki keterampilan berpikir kritis, kreatif, komunikatif, dan kolaboratif. Sistem pendidikan di Indonesia harus mampu beradaptasi untuk membekali siswa dengan kompetensi yang dibutuhkan. Salah satu langkah yang tepat dilakukan untuk menunjang penguasaan keterampilan abad 21 yaitu dengan menerapkan kerangka pembelajaran Community of Inquiry dengan model Think Pair Share. Tujuan penelitian pada artikel ini ada dua. 1) Mengkaji konsep kerangka Community of Inquiry dan model pembelajaran Think Pair Share. 2) Mendeskripsikan penerapan pembelajaran abad 21 melalui kerangka Community of Inquiry dengan model Think Pair Share. Metode penelitian yang digunakan ialah metode kualitatif. Teknik pengumpulan data menggunakan observasi, dokumentasi, dan wawancara. Hasil penelitian pada artikel ini ada dua yaitu 1) Mengetahui konsep kerangka Community of Inquiry dan model pembelajaran Think Pair Share. 2) Penerapan pembelajaran abad 21 melalui kerangka Community of Inquiry dengan model Think Pair Share.